MODELING OF THE HEAT PUMP STATION CONTROLABLE LOOP OF AN INTERMEDIATE HEAT-TRANSFER AGENT (Part II) - Sit M.L.; Andronaty N.R.; Sit B.M> (Problems of the Regional Energetics)
It is studied the model of the heat pump station controllable loop of an intermediate heat-transfer agent for the use in wineries. There are demonstrated transients after the disturbing action of the temperature on the input of cooling jacket of the fermentation stirred tank. There are compared different control laws of the object.